Development of zebrafish chemical screens to identify new modifiers of intestinal neutrophilic inflammation - Silva, Nuno Valério Santos (2022)
Inflammatory bowel diseases (IBD) with chronic infiltration of immune cells in thegastrointestinal tract are common and largely incurable. The therapeutic targeting ofIBD has been hampered by the complex causality of the disease, with environmentalinsults like cholesterol-enriched Western diets playing a critical role. In fact, current therapies are still far from optimal and have significant side effects. This encouragedus to look for alternative approaches like the use of dietary (poly)phenols (PP). PP are known for their anti-inflammatory properties in several chronic inflammatory disordersand are associated with low or absent side effects. However, due to the systemic processing of PP, the most representative molecules that reach the tissues and circulation are low-molecular-weight PP metabolites (LMWPM). Thus, the reported beneficial effects of PP are most likely due to these bioavailable molecules. Yet, the potential for LMWPM in IBD is still unexplored; and the identification of the most potent anti-inflammatory ones can constitute a lead for novel drug development and nutraceutical applications.We developedan easy-to-handle dietary cholesterol-basedin vivoassay that allows the screening of immune-modulatory therapeutics in transgeniczebrafish (ZF) models.ZF larvaewere fed with a highcholesterol diet(HCD),selectively inducingarobust and consistent infiltration of myeloid cells in larvaeintestines that is highly suitable for compound discovery efforts. The use of transgenicswith fluorescent reporter expression in neutrophils, allowedus tomonitor an acute inflammatory response in a whole organismcontext with a fully functional innate immune system. Moreover,semi-automatedimage acquisitionandquantitative image analysis allowedto categorizeanti-or pro-inflammatory compounds based on a leukocytic inflammationindex. Our HCD gut inflammation (HCD-GI) assayis simple, cost-and time-effective aswell as highly physiological.Moreover, analysisof common IBD therapeutics (Prednisolone and Mesalamine) proved the fidelity and clinical relevance of ourIBD-like intestinal inflammation model.Therefore, we took advantage of the HCD-GI assay and implemented a discovery platform to screen a portfolio of 30 LMWPMfor their immune-modulatory properties.We found 4 LMWPM with potent anti-inflammatory properties that strongly halted HCD-induced intestinal inflammation at physiologically relevant concentrations. One, ferulic acid, has been previously reported to have protective and anti-inflammatory functions in animalmodels of IBD.Finally, we developed tools to investigate intestinal functionality under chronic inflammatory states. Specifically, we developed an assay to quantify intestinal motility and peristalsis in ZF larvae after long-term HCD exposure, and a microgavageassay that can be used to investigate the effect of promising metabolites on intestinal barrier function.In conclusion, the HCD-GI discovery platform can facilitate and accelerate drug discovery efforts on IBD, by the identification of novel lead molecules with immune modulatory action on intestinal neutrophilic inflammation. We identified 4 LMWPM with anti-inflammatory potential,whose action is ready tobe investigated in functional assays underchronic feeding settings (out of the current thesis scope). These molecules constitute highly attractive and physiologicallyrelevant strategies worth it to be explored in the future for the nutritional and pharmacological management of IBD.